An insight into mobile advertising and its impact on the resources of handheld devices: a survey. (2019) - Albasir, Abdurhman; Alsabaan, Maazen; Naik, Kshirasagar
With the rapid advancement of mobile devices, people become more attached to them than ever. This growth combined with millions of applications (apps) make smartphones a favourite means of communication among users. The available contents on smartphones, apps and web come into two versions: 1) free contents that are monetised via advertisements (ads); 2) paid ones that are monetised by users' subscription fees. However, the resources on-board are limited and the existence of ads can adversely impact them. These issues brought the need for good understanding of mobile advertising eco-system and how such limited resources should be efficiently used. This survey paper gives an overview on the mobile advertising eco-system and reviews the work done in the regard of the influence of such ads on smartphones' battery life and monthly data usage. It discusses and slightly addresses the open issues and research directions that need to be further investigated. This work is meant to motivate: 1) the researchers to investigate the energy and bandwidth issues further and hence, come up with more practical solutions; 2) app and web developers to consider the seriousness implications of embedding 'expensive' ads in their apps and web-pages on the end users limited resources.